Study on regional differences and convergence of the green development quality of the construction industry: evidence from China - Wang, Jiaming (Frontiers in Environmental Science, 2023)
The green development quality of the construction industry has vital environmental and economic effects. To explore regional differences and convergence, and further provide a reference for the government. Based on the panel data of construction industry development in 31 provinces from 2006 to 2020. This paper measured the green development quality of the construction industry in two-dimensional space-time, focuses on the regional differences, the dynamic evolution trend and the convergence of distribution. The findings supported the fact that the green development quality of construction industry was fluctuating upward trend, the overall difference decreased, and the regional difference showed heterogeneity. The convergence rate in the central region was higher than that in the western region, and there was an obvious ‘catch-up effect’. The green development quality of the construction industry in the national, central region and western region has absolute β convergence. The green development quality of the construction industry in the national, the eastern region and the central region has conditional β convergence. The influence of control variables shows heterogeneity.